2013
DOI: 10.1007/s10433-013-0282-8
|View full text |Cite
|
Sign up to set email alerts
|

Macro- and micro-level predictors of age categorization: results from the European Social Survey

Abstract: This study evaluated macro-and micro-level variables associated with individuals' perception of the ending of youth, the beginning of old age, and the length of the middle age period. The European Social Survey is a biennial multi-country, cross-sectional survey. Our analysis is based on the fourth wave, which included a rotating module on ageism. The source sample consisted of 28 countries and a total of 54,988 respondents. Whereas macro-level variability accounted for 14 % of the variance associated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 66 publications
2
38
0
Order By: Relevance
“…The CCRC is defined as an LTC alternative to functionally independent older adults. Although old age is generally perceived as starting around the age of 64 (Ayalon et al, 2014), the present study suggests that this cut-off is rather young by CCRC standards, with most older adults entering a CCRC after the age of 70 or even 80. This still allows for a very wide range of chronological ages as well as functional, mental and physical ages to be present within the CCRC.…”
Section: Discussionmentioning
confidence: 78%
“…The CCRC is defined as an LTC alternative to functionally independent older adults. Although old age is generally perceived as starting around the age of 64 (Ayalon et al, 2014), the present study suggests that this cut-off is rather young by CCRC standards, with most older adults entering a CCRC after the age of 70 or even 80. This still allows for a very wide range of chronological ages as well as functional, mental and physical ages to be present within the CCRC.…”
Section: Discussionmentioning
confidence: 78%
“…Analysis by Ayalon et al (2014) using the full ESS data confirmed that 14% of the total variance in the perceived end of youth was associated with differences between countries, while only 5.7% of the total variance in the perceived onset of old age was associated with differences between countries. In addition to the previous study, the authors found that having better subjective health and living with a spouse or partner was also associated with perceiving the end of youth to be later, while higher levels of education, better subjective health, higher life satisfaction and sharing a residence with a spouse or partner were all associated with perceiving old age to be later.…”
Section: Age Categorisationmentioning
confidence: 91%
“…On average, across the 29 countries, respondents perceived youth to end at 40 years and old age to begin at 62, this may mean that people below 40 years and over 62 years are more vulnerable to age prejudice and discrimination due to their perceived 'young' or 'old' age, respectively. However, the placement of these age boundaries varies by respondent's own age, the self-categorization of their age, gender and the country in which they live (Abrams et al 2011a;Ayalon et al 2014;Basleven 2010), such that both perceptions of the end of youth and onset of old age increase with respondents' age. In addition, respondents who self-categorized themselves as belonging to a younger age group (relative to those who are the same chronological age) also perceived old age to start later (Basleven 2010).…”
Section: Age Categorisationmentioning
confidence: 99%
See 1 more Smart Citation
“…I expect the relationships between these individual-level characteristics and religious non-affiliation to vary across nations. The social and cultural implications of gender (Inglehart and Norris, 2003), age (Ayalon et al, 2014), marital status (Cooke and Baxter, 2010), and education (Schwadel, 2015) differ across nations. What it means to be old or young, a man or woman, college or not college educated, and married or single are context specific.…”
Section: The Social Origins Of Religious Non-affiliationmentioning
confidence: 99%